2014
DOI: 10.1371/journal.pone.0090337
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of miR-34a Attenuates Cardiac Dysfunction in a Setting of Moderate, but Not Severe, Hypertrophic Cardiomyopathy

Abstract: Therapeutic inhibition of the miR-34 family (miR-34a,-b,-c), or miR-34a alone, have emerged as promising strategies for the treatment of cardiac pathology. However, before advancing these approaches further for potential entry into the clinic, a more comprehensive assessment of the therapeutic potential of inhibiting miR-34a is required for two key reasons. First, miR-34a has ∼40% fewer predicted targets than the miR-34 family. Hence, in cardiac stress settings in which inhibition of miR-34a provides adequate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 47 publications
(81 reference statements)
4
68
2
2
Order By: Relevance
“…In settings of established cardiac injury, it is likely that antagonism of miR-34a alone is insufficient to promote cardiac regeneration, and a more broad inhibition of miR-34 family members is required. 19, 33 …”
Section: Discussionmentioning
confidence: 99%
“…In settings of established cardiac injury, it is likely that antagonism of miR-34a alone is insufficient to promote cardiac regeneration, and a more broad inhibition of miR-34 family members is required. 19, 33 …”
Section: Discussionmentioning
confidence: 99%
“…Whilst most investigators examine the potential of inhibiting miRNAs that have increased expression in a cardiac disease setting (see review [55]), Bernardo and colleagues therapeutically target miRNAs that display differential expression in settings of cardiac stress and protection [6467]. Inhibition of miR-34, miR-34a, or miR-652 with miRNA inhibitors was associated with reduced pathology and improved cardiac function in mouse models of cardiac disease via mechanisms that are associated with preserved angiogenesis, decreased fibrosis and a more favourable cardiac molecular profile (e.g.…”
Section: Targeting Non-coding Rnas For the Treatment Of Heart Failurementioning
confidence: 99%
“…Inhibition of miR-34, miR-34a, or miR-652 with miRNA inhibitors was associated with reduced pathology and improved cardiac function in mouse models of cardiac disease via mechanisms that are associated with preserved angiogenesis, decreased fibrosis and a more favourable cardiac molecular profile (e.g. attenuation of ANP, BNP gene expression) [6466]. Further, treatment with these miRNA inhibitors was associated with upregulation of target genes implicated in angiogenesis, contractile function and cell survival [65, 66].…”
Section: Targeting Non-coding Rnas For the Treatment Of Heart Failurementioning
confidence: 99%
“…Each of these miRNAs, or their family members, have previously been shown to be elevated in hearts of cardiac stress mouse models associated with fibrosis (e.g., MI, pressure overload, dilated cardiomyopathy and atrial fibrillation), and targeting these miRNAs was effective in preventing or attenuating fibrosis in vivo (5,(7)(8)(9)(10)(11)(12)(13)(14). Other studies have identified numerous additional miRNAs dysregulated in cardiac fibrotic models.…”
Section: Other Mirnas Implicated In Regulating Cardiac Fibrosismentioning
confidence: 99%